The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5923/j.ajcmp.20120201.01
|View full text |Cite
|
Sign up to set email alerts
|

Computational Investigation of Electronic and Optical Properties of Si, Ge and Si1-xGex Alloys Using the FP-LMTO Method Augmented by a Plane-Wave Basis

Abstract: An investigation into the structural, electronic and optical properties of Si, Ge, and Si 1-x Ge x for different compositions was conducted using first-principles calculations based on density functional theory (DFT). The total energies were calculated within the full-potential linear muffin-tin orbital (FP-LMTO) method augmented by a plane-wave basis (PLW), implemented in Lmtar code. The effects of the approximations to the exchange-correlation energy were treated by the local density approximation (LDA). Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…In our previous publication [22], we were interested to the investigation of the structural, electronic and optical properties of Si, Ge, and Si 1-x Ge x for different compositions using the full-potential linear muffin-tin orbital (FP-LMTO) method augmented by a plane-wave basis (PLW), implemented in Lmtar code [23][24][25]. All the obtained results showed that the weakly strained G-rich SiGe layers possess very promising properties for both electronic and optical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous publication [22], we were interested to the investigation of the structural, electronic and optical properties of Si, Ge, and Si 1-x Ge x for different compositions using the full-potential linear muffin-tin orbital (FP-LMTO) method augmented by a plane-wave basis (PLW), implemented in Lmtar code [23][24][25]. All the obtained results showed that the weakly strained G-rich SiGe layers possess very promising properties for both electronic and optical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Since GexSi1-x is an excellent TE material, this literature review begins with the study of TE materials. Literatures [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][56][57][58][59][60][61][62][63][64][65][66][67] are selected to help study the fundament and the When comparing the experimental data 10 and calculation data [11][12][13] , tt can be observed that conventional GGA-PBE and LDA methods often incur errors when calculating the band gap of GexSi1-x. Therefore, another ab-initio band gap calculation method for GexSi1-x is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental research across the properties of GexSi1-x series alloy system including band gap has been published in the past 10 , and several calculation works have also been performed [11][12][13] . Most of these calculations are based upon exchange-correlation energy functional approximations, and some of these are the local-density approximation (LDA) 14 and the Generalized Gradient Approximation (GGA) 15 with the Perdew-Burke-Ernzerhof (PBE) form 16 .…”
Section: Improvements In Calculation Methodsmentioning
confidence: 99%